2021
DOI: 10.3746/pnf.2021.26.1.67
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Quercetin and Resveratrol on Zinc Chloride- and Sodium Metavanadate-Induced Passive Avoidance Memory Retention Deficits in Male Mice

Abstract: Quercetin and resveratrol are found in a variety of fruits and vegetables and have several biological and pharmacological properties. In this study, the effects of quercetin [50 mg/kg, intraperitoneal (i.p.)] and resveratrol (50 mg/kg, i.p.) on zinc chloride (ZnCl2; 75 mg/kg/d, 2 weeks oral gavage) and sodium metavanadate (SMV; 22.5 mg/kg/d, 2 weeks oral gavage) induced passive avoidance memory retention were investigated in step-through passive avoidance tasks. ZnCl2 was dissolved in saline and SMV was dissol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 97 publications
2
0
0
Order By: Relevance
“…The activation of Sirt1 by VitD3 has been observed to also strengthen the neuronal synapse, cause a decrease in AChE activity, reduce oxidative stress, and downregulate NF-kB, TNF-α, and IL-1 79 83 . Our results indicate that Res significantly improves memory deficits in ET rats, which is in line with previous studies 84 , 85 , including those that showed that Res improved performance in the passive avoidance task in a model of Alzheimer’s disease. Res was believed to exert its beneficial effects on impairments in recognition memory by enhancing activity in cholinergic systems, increasing levels of BDNF, facilitating phosphorylation of cAMP response element binding protein (CREB) signaling pathways in the prefrontal cortex, inhibiting the production of inflammatory cytokines, and reducing oxidative stress 84 89 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The activation of Sirt1 by VitD3 has been observed to also strengthen the neuronal synapse, cause a decrease in AChE activity, reduce oxidative stress, and downregulate NF-kB, TNF-α, and IL-1 79 83 . Our results indicate that Res significantly improves memory deficits in ET rats, which is in line with previous studies 84 , 85 , including those that showed that Res improved performance in the passive avoidance task in a model of Alzheimer’s disease. Res was believed to exert its beneficial effects on impairments in recognition memory by enhancing activity in cholinergic systems, increasing levels of BDNF, facilitating phosphorylation of cAMP response element binding protein (CREB) signaling pathways in the prefrontal cortex, inhibiting the production of inflammatory cytokines, and reducing oxidative stress 84 89 .…”
Section: Discussionsupporting
confidence: 93%
“…Our results indicate that Res significantly improves memory deficits in ET rats, which is in line with previous studies 84 , 85 , including those that showed that Res improved performance in the passive avoidance task in a model of Alzheimer’s disease. Res was believed to exert its beneficial effects on impairments in recognition memory by enhancing activity in cholinergic systems, increasing levels of BDNF, facilitating phosphorylation of cAMP response element binding protein (CREB) signaling pathways in the prefrontal cortex, inhibiting the production of inflammatory cytokines, and reducing oxidative stress 84 89 . Recent studies have shown that Sirt1 plays a key role in cognitive performance and regulation of memory function through modulation of BDNF and inhibition of glutamate and the glutamatergic NMDA receptors, which are important factors in the differentiation of hippocampal neuronal cells and synaptic plasticity 90 .…”
Section: Discussionsupporting
confidence: 93%
“…Quercetin (3,3 ,4 ,5,7-pentahydroxyflavone) is a flavonol abundantly present in various vegetables and fruits [173]. It can protect against multiple diseases, such as osteoporosis, cancer, memory impairment, and cardiovascular diseases, and these promising effects are achieved partly through its antioxidant and anti-inflammatory actions [174][175][176][177]. Quercetin also has a positive influence on decreasing body weight and adiposity in diet-induced obese animals, and multiple mechanisms, such as the activation of lipolysis, inhibition of lipogenesis and adipogenesis, and browning effects, have been implicated in its antiobesity effects in vivo and in vitro [178][179][180][181][182][183][184].…”
Section: Quercetinmentioning
confidence: 99%